Characteristics of Effective Teaching in Canadian Universities- An Analysis based on the Testimony of a Thousand Graduates - Sheffield, Edward F. (Canadian Journal of Higher Education, 1974)
A thousand graduates of nineteen Canadian universities, in a variety of disciplines, re- sponded to an invitation to name the professors they remembered as excellent teachers and to say why. Analyses of their comments reveal what they considered to be characteristics of effective university teaching. Comparisons of various sub-groups suggest that there are some differences in the patterns of good teaching between anglophone and francophone faculties and between fields of study—humanities, social sciences, biological sciences and physical sciences—but the patterns are basically similar in most university settings.